Design, synthesis of imidazole scaffolds as an effective larvicidal agent against Etiella zinkenella and in vitro antibacterial and antifungal evaluation against Candida albicans with DFT calculations, molecular docking technique and theoretical biological potential - Ankita M. Rayate; Manoj R. Gaware; Dnyaneshwar D. Lokhande; Amol H. Kategaonkar; Arun M. Bhagare; Bharat N. Shelke; Avinash S. Kale; Sapana S. Bhamare (Results in Chemistry)
In this paper we have reported synthesis evaluation imidazole by solvent free multi component scaffolds (NEAT Reaction) by simple and very effective protocol. The characterization of compounds by 1H NMR, 13C NMR, Mass and IR spectral studies confirms the structure. The theoretical interpretations of compounds is optimized by 6–311++G (d,p) basic set for employing different parameters using Gaussion-09 software. The antimicrobial activity associated with all the imidazole derivatives showed mild activity towards E. coli, S. typhi and Staphylococcus aureus while good microbial activity against P.vulgaris. The compounds showed promising antifungal activity against Candida albicans. The bioactivity against Etiella zinkenella was evaluated. Significant results were obtained with notable larvicidal activity having Lethal concentration (LC50) = 0.38 ppm associated with compound 6a with concentration ranging between 0.02‐and 0.08 ppm. Molecular docking of imidazole compounds were done to study the protein interaction and enzyme inhibitor activity. Docking analysis was performed using Autodoc Vina and visualized in Pymol software compound. The study suggested that compound 6d and 6e showed good bonding affinity to an enzyme exhibiting highest affinity (binding energy = −6.5 to 6.8 kcal/mol) with protein (4MCT) of P.vulgaris organism. Excellent affinity with binding energy −6.1 kcal/mol with protein (5AEZ) is associated with Candida albicans for compound 6b, 6c, 6e and 6 f. The PASS analysis is web-based application used predict the biological activity spectrum of a compound based on structure. It is useful to estimate the probable biological activity profile. The PASS analysis shows that compound 6b shows high activity for Antieczematic and Gluconate 2-dehydrogenase (acceptor) inhibitor (Pa > 0.07).